Fate of vaccines of Propionibacterium acnes after phagocytosis by murine macrophages. - Pringle, A T (1982)
Stationary-phase (48 h) cells of Propionibacterium acnes VPI 0009, a potent stimulator of the reticuloendothelial system, persist unchanged within phagocytes for at least 24 h after ingestion. In contrast, exponential-phase (12 h) cells of the same strain (which do not induce splenomegaly) are extensively degraded within 5 h of phagocytosis. Suspensions of P. granulosum VPI 6500, which fails to induce splenomegaly in mice, also show considerable degradation after phagocytosis. Stationary-phase cells of strain VPI 0009 treated with sodium metaperiodate or with trichloroacetic acid, although without ability to induce splenomegaly, resist destruction almost as well as untreated vaccines. However, bacteria inactivated by acetic anhydride show about 50% breakdown in 24 h.